Analysis of junior high school students critical thinking skills in solving contextual-based problems - Padilah, Elvira Barokah; Imswatama, Aritsya; Balkist, Pujia Siti (Universitas Sarjanawiyata Tamansiswa, 2025)
Critical thinking skills involve analysis, evaluation, and reasoning—essential abilities that students need to navigate the challenges of globalization. However, many students still lack adequate critical thinking skills. This is evident from the 2022 Program for International Student Assessment (PISA) results, which indicate that Indonesian students' PISA scores remain low. Contextual questions, as tested in PISA, can serve as an effective tool for measuring students' critical thinking abilities. This study aims to analyze the critical thinking skills of junior high school students in solving contextual-based mathematics problems, particularly those aligned with the PISA framework. The research employs a quantitative descriptive method, administering six descriptive questions on the topic of curved surface geometry to 37 ninth-grade students at SMP Negeri 12 Sukabumi City. The findings reveal that 11% of students exhibit high critical thinking skills, 30% demonstrate moderate skills, and 59% possess low skills. Students' responses indicate that they struggle to meet the five critical thinking indicators: identifying, clarifying, analyzing, evaluating, and inferring. Based on data analysis, it can be concluded that the critical thinking ability of students at SMP Negeri 12 Sukabumi City remains low, with 59% of students categorized in the low-skill group. This study contributes to the understanding of students' critical thinking deficiencies and highlights the need for improved teaching strategies to enhance these essential skills.